2022
DOI: 10.1155/2022/2606781
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Smart Watch and System Construction Method for the Elderly Based on Big Data

Abstract: Under the development trend of artificial intelligence and smart city, efforts should be made to improve the connection between the elderly and social development and realize the application of intelligence to travel for the elderly so that the elderly can also enjoy an intelligent and convenient life. With the deepening of China’s aging population, a systematic re-innovative design of smart watches was carried out based on the physiological needs of the elderly living alone in cities. In order to solve the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, some studies proposed better intelligent product designs of wearable devices for older adults. For instance, Zhu et al [58] redesigned a smartwatch for older adults that integrated a system that allowed for user self-management. The design involved daily monitoring assistance from a physician and a customized preventive rehabilitation program based on the latest data.…”
Section: The Products' Ease Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some studies proposed better intelligent product designs of wearable devices for older adults. For instance, Zhu et al [58] redesigned a smartwatch for older adults that integrated a system that allowed for user self-management. The design involved daily monitoring assistance from a physician and a customized preventive rehabilitation program based on the latest data.…”
Section: The Products' Ease Of Usementioning
confidence: 99%
“…However, the study did not provide feedback from older adults on the device's ease of use or discuss the interface data. Zhu et al and Guner and Albayrak [57,58] demonstrated wearable watches' interactive designs in terms of accelerated data recognition, which was used to capture information accurately and transmit it to relatives promptly. In another study, Lin et al [29] created an improved design for smart insoles that allowed for activity recognition, telemedicine detection, and health assessment.…”
Section: The Products' Ease Of Usementioning
confidence: 99%
“…Smart products could act as a bridge between users and these sophisticated technologies (Zhu et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Smart products could act as a bridge between users and these sophisticated technologies (Zhu et al, 2022). As a popular product of smart technology, smartwatch marketing and usage ecosystem could be viewed as a combination of three main components.…”
mentioning
confidence: 99%